Cover Image. Issue 7 (1st July 2022) - Li, Shuting; Fan, Ting; Li, Chao; Wang, Yunfeng; Li, Jian; Liu, Zhiyong
Abstract : Triple immunostaining of hair cell specific marker Myo6 (green), HA (Atoh1, white) and Tdtomato (red) in cryosection saccular organs of the Atoh1 ‐3*HA‐P2A‐Cre/+ ; Ai9/+ embryos at E13.5. Tdtomato marks the cells in the sensory region that experience Atoh1 mRNA expression, whereas HA labels the nascent HCs or HC progenitors expressing high level of Atoh1 protein; From: Fate‐mapping analysis of cochlear cells expressing Atoh1 mRNA via a new Atoh1 3*HA‐P2A‐Cre knockin mouse strain . Li S, Fan T, Li C, Wang Y, Li J, Liu Z; Dev Dyn. 251(7):1156‐1174. https://doi.org/10.1002/dvdy.453